2016
DOI: 10.18632/oncotarget.10476
|View full text |Cite
|
Sign up to set email alerts
|

Snail promotes resistance to enzalutamide through regulation of androgen receptor activity in prostate cancer

Abstract: Treatment with androgen-targeted therapies can induce upregulation of epithelial plasticity pathways. Epithelial plasticity is known to be important for metastatic dissemination and therapeutic resistance. The goal of this study is to elucidate the functional consequence of induced epithelial plasticity on AR regulation during disease progression to identify factors important for treatment-resistant and metastatic prostate cancer. We pinpoint the epithelial plasticity transcription factor, Snail, at the nexus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 55 publications
(62 reference statements)
4
44
1
Order By: Relevance
“…Based on our preclinical data and these observations, we hypothesized that p38 activation would be associated with aggressive and metastatic disease. To test our hypothesis we compared, by immunohistochemistry, 30 primary tumors and 20 metastatic biopsies from prostate cancer patients (Ware et al, 2016) for phospho-p38 expression. These tumors were all positive for AR expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our preclinical data and these observations, we hypothesized that p38 activation would be associated with aggressive and metastatic disease. To test our hypothesis we compared, by immunohistochemistry, 30 primary tumors and 20 metastatic biopsies from prostate cancer patients (Ware et al, 2016) for phospho-p38 expression. These tumors were all positive for AR expression.…”
Section: Resultsmentioning
confidence: 99%
“…To better understand the mechanisms by which p38 activity may promote metastasis, we interrogated known drivers of metastatic prostate cancer. One of these drivers of metastasis is Snail, a master regulator of epithelial plasticity that promotes migration and invasion and is strongly expressed in 100% of metastatic prostate cancer biopsies (Ware et al, 2016). We have previously shown that Snail activates AR nuclear localization to drive plasticity, invasion, and enzalutamide resistance (Ware et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of Snail in MDCK and many carcinoma cell lines led to loss of cell-cell adhesion mediated by E-cadherin, transformed the morphology of cells from epithelial to spindle-liked mesenchymal, and enhanced their migratory and invasive traits in vitro (Batlle et al, 2000;Cano et al, 2000). Further work revealed a similar, but less potent role of another EMT-TF Slug (SNAI2, a member of Snail family) both in vitro and in vivo (Bolós et al, 2003;Hajra et al, 2002;Ware et al, 2016). Snail was also shown to induce the expression of mesenchymal markers fibronectin and Zeb1 (Guaita et al, 2002), the latter of which is another EMT-TF that can promote tumor invasiveness in vitro and is correlated with tumor cell differentiation in vivo (Aigner et al, 2007;.…”
Section: Role Of Emt-tfs In Metastasis: Necessary or Permissive?mentioning
confidence: 99%
“…Twist1/AR signaling is also augmented in castration resistant as well as mesenchymal-type PCa, indicating the molecular mechanism of mutual and functional crosstalk between EMT and castration resistance [125]. The EMT master regulator, Snail, promotes enzalutamide resistance and mPCa, as a consequence of increased full-length AR and AR-V7 expression and nuclear localization, in preclinical models of PCa and in patients [126]. On the other hand, ligand-activated AR regulates expression of several key EMT factors whereas antiandrogens counteract AR activity only on selected EMT genes [127].…”
Section: Potential Therapeutic Intervention Of Pca Metastasismentioning
confidence: 99%